Anthropometric assessment of patients with cerebral palsy: Which curves are more appropriate? - Liubiana A. Araújo; Luciana R. Silva (Brazilian Society of Pediatrics, 2013)
Objective: To describe the nutritional assessment of children with cerebral palsy, verifying the correlation of growth curves specific for cerebral palsy with general curves, in addition to assessing the presence of digestive manifestations associated with nutritional problems. Methods: This was a cross-sectional study of 187 individuals with cerebral palsy, evaluating anthropometric data in curves commonly used in pediatrics and specific curves for cerebral palsy, in addition to the description of presence of dysphagia, constipation, and respiratory infections. Results: 58% of patients were males, with a mean age of 5.6±3.5 years. Anthropometric data of weight below the 10th percentile occurred in 10% of the sample considering the cerebral palsy scale, versus 51% when considering the reference from the Centers for Disease Control and Prevention (p < 0.01; Kappa 0.19). The weight of most individuals with dysphagia, recurrent respiratory infections, and constipation was below the 50th percentile, with respective percentages of 67%, 75%, and 72%. Conclusion: The references commonly used in pediatrics tend to overestimate malnutrition in individuals with cerebral palsy, and their correlation with specific references for cerebral palsy is low. Digestive manifestations were mainly found in those individuals whose anthropometric measurements were below the 50th percentile.